Thermal decomposition derived nano molybdenum nitride for robust counter electrode in dye-sensitized solar cells - Sudhagar Pitchaimuthu (Materials Today Communications, 2021)
The unique category of transition metal nitrides has an immense scope as an electron-driven catalyst in redox reactions. However, synthesizing metal nitrides without contamination is very challenging. The residues present in the catalyst might affect catalytic activity. This work reports a simple synthesis of contamination-free nanoscale molybdenum nitride (Mo2N) powder by integrated wet chemical and thermal decomposition techniques at 800 ̊C. Systematic structural and morphological studies were done, which shows the spherical shape of -Mo2N nanoparticles. Electrochemical and photovoltaic characteristics were studied using cyclic voltammetry, electrochemical impedance spectroscopy (EIS), Tafel polarization and J-V characteristics. As a result of high electrolyte diffusivity, less charge transfer resistance, high electrochemical stability and catalytic activity, the nano Mo2N based DSSCs exhibits 5.3% efficiency, which is comparable to Pt-based device (6.4%) fabricated under the similar condition that is 83.7% of the performance offered by an expensive counter electrode. This simple synthesis method could enable low-cost mass production of Mo2N nanoparticles as counter electrodes in DSSC. The developed counter electrodes may be a suitable alternative for stable, efficient and low-cost DSSCs.